1994
DOI: 10.1111/j.1600-0447.1994.tb01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological abnormalities in patients with schizophrenia or schizophreniform disorder at first admission to hospital: correlations with computerized tomography and regional cerebral blood flow findings

Abstract: Forty-five patients with schizophrenia or schizophreniform disorder admitted to hospital for the first time had a neurological examination, including integrative sensory and complex motor acts, by a trained neurologist. The patients were studied by CT (computerized tomography) and rCBF (regional cerebral blood flow) as well. A control group of 24 healthy volunteers was included. The patients had significantly more neurological abnormalities (NA) than the healthy volunteers. Medication did not explain the discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 21 publications
2
30
0
2
Order By: Relevance
“…However, the underlying cerebral changes have not yet been fully identified. Limited structural brain imaging from western samples suggest that neurological soft signs are associated with enlargement of cerebral ventricles [42], smaller brain areas [43], particularly in grey matter involving in sub-cortical regions such as putamen, globus pallidus and thalamus as well as cerebellum [44][45][46][47][48]. A similar reduction in grey matter volumes in these regions was also demonstrated in healthy volunteers [49].…”
Section: Illustration Of Neurological Soft Signs As An Example From Cmentioning
confidence: 55%
“…However, the underlying cerebral changes have not yet been fully identified. Limited structural brain imaging from western samples suggest that neurological soft signs are associated with enlargement of cerebral ventricles [42], smaller brain areas [43], particularly in grey matter involving in sub-cortical regions such as putamen, globus pallidus and thalamus as well as cerebellum [44][45][46][47][48]. A similar reduction in grey matter volumes in these regions was also demonstrated in healthy volunteers [49].…”
Section: Illustration Of Neurological Soft Signs As An Example From Cmentioning
confidence: 55%
“…Moreover, several studies found that overall neurological impairment was related to severity of negative symptoms (e.g., Yazici et al, 2002;Scheffer, 2004). However, a few studies (e.g., Bartko, Zador, Horvath, & Herezeg, 1988;Rubin et al, 1994;Chen, Lam, Chen, & Nguyen, 1996) failed to find a significant relation between negative symptoms and neurological impairment. Bombin et al suggested that these studies did not include tasks that assessed neurological soft signs in the domains of motor sequencing and sensory integration.…”
Section: Neurological Soft Signs and Schizophreniamentioning
confidence: 99%
“…3,4 Studies have been conducted to investigate the regional cerebral flood flow (rCBF), especially in the frontal lobe, of both normal subjects and schizophrenic patients while tak-ing the WCST. [5][6][7][8][9][10][11][12][13] Rezai et al showed that the WCST primarily activates the left dorsolateral prefrontal cortex of normal adults. 14 Nevertheless, Cantor-Graae et al found no significant prefrontal flow augmentations during performance of the WCST of healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%